2014
DOI: 10.1001/jamasurg.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission After Noncardiac Surgery

Abstract: Unplanned readmissions in surgical patients are common in patients experiencing postoperative complications and can be predicted using the ACS NSQIP risk of major complications. Prospective identification of high-risk patients, using the NSQIP complication risk index, may allow hospitals to reduce unplanned rehospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 25 publications
9
101
0
Order By: Relevance
“…This relationship has been well described previously. [28][29][30] We found a correlation between MSH and readmission, which is also in agreement with other studies. 7,8 Although we initially suspected that greater rates of complication in MSH settings might explain our findings, we instead found that complication rates do not vary significantly between MSH and non-MSH for any procedure.…”
Section: Discussionsupporting
confidence: 93%
“…This relationship has been well described previously. [28][29][30] We found a correlation between MSH and readmission, which is also in agreement with other studies. 7,8 Although we initially suspected that greater rates of complication in MSH settings might explain our findings, we instead found that complication rates do not vary significantly between MSH and non-MSH for any procedure.…”
Section: Discussionsupporting
confidence: 93%
“…The overall rate of readmission of 4.7% compares very favourably with the 6.8% readmission rate found in a recent study based on the NSQIP database 8 . The majority of readmissions (57%) were related to surgical site or abdominal septic complications, with most of these (70%) requiring surgical or radiological intervention.…”
Section: Discussionsupporting
confidence: 73%
“…It may be surprising that reductions in medical and surgical readmission are associated, as a growing body of work suggests that surgical and medical readmissions have different underlying mechanisms. [1][2][3][19][20][21] However, it is possible that HRRP motivated hospital leaders to prioritize readmission reductions, and that this could have resulted in the implementation of department specific approaches which had an effect on reducing both non-targeted and targeted surgical procedures. In fact, a prior study found that two-thirds of hospital leaders in the U.S. believed that the HRRP had a "major impact" on the implementation of system wide strategies to reduce readmission rates.…”
Section: Discussionmentioning
confidence: 99%